Hadith Tarbawi Learning Model in Forming Students' Pancasila Character - Arcanita, Rapia; Warsah, Idi; Karolina, Asri; Indrawari, Karliana (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study aims to understand the role of character education in higher education in forming students' identity, independence, and responsibility, as well as integrating Pancasila values to enhance the quality of human resources. This study employs a field research design with a grounded theory approach. The participants in this study are lecturers from the Islamic Education program (PAI) at the Faculty of Education/Tarbiyah at IAIN Curup. The primary data sources are lecturers teaching Hadith Tarbawi and students from the PAI program, while secondary data includes lesson plans (RPS), books, and other written materials related to the research. Data collection techniques include observation, interviews, documentation, and literature study. Data analysis techniques involve open coding, axial coding, selective coding, and memoing. The results of this study indicate that the